Causes and consequences of corruption: the context of Asia - Chua, Xiang Xin (2020)
Corruption is receiving a lot of attention globally and researchers have been discussing issues related to the causes and consequences. This paper investigates the effect of government size on corruption, and further confirm the consistency of the initial model by investigating whether additional independent variables such as democracy, economic freedom and economic growth would produce a better model. Using annual data from 27 countries between 2007 to 2016, empirical results indicate that a larger government size will lead to lower level of corruption. The result is consistent in the enhanced model and surprisingly we have discovered that democracy, one of the widely discussed factor, is not significant to corruption.